2016
DOI: 10.2147/ott.s114229
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin functions as an oncogene in human gliomas by promoting cell migration and invasion

Abstract: BackgroundPaxillin is implicated in tumorigenesis, progression and aggressive phenotypes of various malignancies, highlighting its functions in cellular adhesion, migration and survival. However, the roles of paxillin in human gliomas remain unclear. The aim of this study was to evaluate the clinical implication of paxillin expression in patients with gliomas and its biological function in glioma cells.Patients and methodsExpression levels of paxillin gene and protein, respectively, were detected by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Only GD3 formed a molecular complex with PDGFRα, and the Src family Yes was also included in the complex, leading to the formation of a ternary molecular complex adjacent to the cell membrane . This complex activated paxillin, resulting in the increased invasiveness that is the most notable feature of gliomas (Figure A).…”
Section: Cancer‐associated Glycosphingolipids Play Roles Through Compmentioning
confidence: 99%
“…Only GD3 formed a molecular complex with PDGFRα, and the Src family Yes was also included in the complex, leading to the formation of a ternary molecular complex adjacent to the cell membrane . This complex activated paxillin, resulting in the increased invasiveness that is the most notable feature of gliomas (Figure A).…”
Section: Cancer‐associated Glycosphingolipids Play Roles Through Compmentioning
confidence: 99%
“…Besides EMT, mobility and cell migration via integrin and FAK play an important role in metastasis (36,37). In addition, the roles of FAK, PXN and VCL in cancer cell invasion and motility have already been studied (35,38,39). However, the role of FAK, PXN and VCL is not clear in the heterogeneity of breast cancer cells.…”
Section: Figure 5 Expression Of Focal Adhesion Markers In Single-celmentioning
confidence: 99%
“…Phospholipase C signaling is also associated with cell proliferation as well as CXCR4 35 . Rac, RhoA, Cdc42 and other signaling pathways by Rho family GTPases are associated with glioma invasion 36 , and paxillin signaling is associated with migration and invasion 37 . It has been reported that PI3K and ERK/MAPK signaling mediate induction of HIF-1α 38 .…”
Section: Discussionmentioning
confidence: 99%